2021
DOI: 10.7717/peerj.11674
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertilizer and biochar applications on the relationship among soil moisture, temperature, and N2O emissions in farmland

Abstract: Background Di-nitrogen oxide (N2O) emissions from soil may lead to nonpoint-source pollution in farmland. Improving the C and N content in the soil is an excellent strategy to reduce N2O emission and mitigate soil N loss. However, this method lacks a unified mathematical index or standard to evaluate its effect. Methods To quantify the impact of soil improvement (C and N) on N2O emissions, we conducted a 2-year field experiment using biocha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
3
5
0
Order By: Relevance
“…However, biochar and ash amended treatments did not impact N 2 O emissions. This confirms previous studies as biochar adsorbed inorganic N, thus decreasing the N concentration available for nitrification and denitrification, thus reducing N 2 O emissions (Wang et al, 2021). In addition, the use of N-fertilizers directly influences the amount of NH 4 + or NO 3 − available in the soil.…”
Section: Resultssupporting
confidence: 91%
“…However, biochar and ash amended treatments did not impact N 2 O emissions. This confirms previous studies as biochar adsorbed inorganic N, thus decreasing the N concentration available for nitrification and denitrification, thus reducing N 2 O emissions (Wang et al, 2021). In addition, the use of N-fertilizers directly influences the amount of NH 4 + or NO 3 − available in the soil.…”
Section: Resultssupporting
confidence: 91%
“…Increase in soil moisture in conservational land preparation was due to reduced soil disturbance which maintained the soil structure and soil water percolation. This is in agreement with [23,30] who found that conservational land preparation method increased soil moisture content significantly by 8%, 4.4% and 8.5%.…”
Section: Effects Of Land Preparation Methods and Organic Amendment On...supporting
confidence: 92%
“…No-tillage and reduced tillage techniques increases the effectiveness of water usage and lower evapotranspiration in cereals [21,22]. Zero-tillage method has been found to conserve soil moisture up to 32%, which has been found to increase maize yields up to 17% [23]. In Kenya the common method of land preparation being used is conventional tillage method, minimum tillage and ridging method to enhance moisture conditions in semi-humid regions [24].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the unreasonable use of natural resources by humans, the cycle of carbon and nitrogen in the biosphere has been accelerated 2 , the stability of carbon and nitrogen in the soil has been changed, and the concentration of greenhouse gases has continued to increase, resulting in the greenhouse effect, which has become a relevant focus of general attention in the field 3 . N 2 O is a major greenhouse gas, 80% to 90% of N 2 O in the atmosphere emits from cultivated soils annually, and cultivated soils are a significant source of emissions 4 . Studies have shown that the main pathways for the production of N 2 O in agricultural soil are nitrification and denitrification processes.…”
Section: Introductionmentioning
confidence: 99%